Development and validation of a self-administered neck mobility assessment tool (S-ROM-Neck) in chronic neck pain patients. (October 2018) - Langenfeld, Anke; Bastiaenen, Caroline; Sieben, Judith; Swanenburg, Jaap
Abstract: Background: Cervical spine (CS) range of motion (ROM) is commonly used to assess neck pain. However, this measurement is often limited by the clinician's experience and perception. Therefore, the integration of perceptual feedback of the patient can optimize and personalize treatment. Objective: Develop and validate a questionnaire (S-ROM-Neck) to evaluate ROM of the CS from the patient's perspective. Design: Validation study. Methods: The assessment tool was developed and optimized during pretest sessions. Reliability and construct validity of the questionnaire were tested. 50 participants (age >18 years) with neck pain for >90 days, able to fluently speak, read, and write in German were included. Exclusion criteria included any condition that limited manual therapy to the CS. Participants completed S-ROM-Neck twice within seven days, along with the visual analogue scale (VAS) for pain intensity and the German version of the Neck Disability Index (NDI-G). The relative reliability, internal consistency, and absolute reliability were analyzed, and Bland–Altman plots were generated. Construct validity was established by correlating the total score of S-ROM-Neck with VAS and NDI-G based on pre-set hypotheses. Results: S-ROM-Neck demonstrated moderate reliability with an intraclass correlation coefficient of 0.718 (Cronbach's alpha of 0.83). There was a medium negative correlation between VAS and S-ROM-Neck [Spearman's rank correlation coefficient (rs ) = −0.30, p  = 0.031] and the NDI-G and S-ROM-Neck (rs  = −0.40, p  = 0.002). Conclusions: These results indicate the reliability and internal consistency of S-ROM-Neck. This scale provides patient feedback and perspectives to optimize assessment of neck pain. Highlights: The patient's perspective can add valuable insights into a patient's complaint. The S-ROM-Neck is a newly developed measurement tool, to assess the patient's perspective on cervical spine range of motion. The S-ROM-Neck has shown to be valid and reliable.